A longitudinal study of aroma evolution in coffee‐flavoured milk using gas chromatography–olfactometry. (14th March 2022) - Pandohee, Jessica; Thornton, Megan; Keast, Russell
Abstract : This paper provides a longitudinal assessment of aroma evolution of coffee‐flavoured milk over a four‐week period using gas chromatography–olfactometry. A total of 52, 48, 55 and 48 aroma‐active compounds were perceived in week 1, 2, 3 and 4, respectively. Across the four weeks, 90 unique compounds were detected. Of those 90 compounds, it was found that 64 contributed to a 'pleasant' aroma and18 to a 'disagreeable' aroma. The work presented in this paper will be of interest to food scientists working with dairy products, with an interest in flavour development throughout shelf‐life from a sensory perspective. Abstract : Changes in aroma and flavour of coffee‐flavoured milk.